Credit Growth in Sub-Saharan Africa-Sources, Risks, and Policy Responses - Khamis, May (IMF Working Papers; Working Paper ;, 2009)
In this paper, we analyze credit growth in Sub-Saharan Africa over the past decade focusing on the post-2002 rapid credit growth in select countries. We develop regression models of the fundamental determinants of bank credit and use them to examine whether they can fully explain developments in rapid credit growth countries. We then argue that rapid credit expansion, whether a manifestation of a credit boom or driven by fundamentals, can give rise to prudential and macroeconomic risks. We detail these risks and discuss the choice of policies to mitigate them. We conclude by evaluating the likely impact of the ongoing global recession and financial crisis on credit growth in Sub-Saharan Africa.